Kajian Yuridis Mengenai Pemberian Remisi Bagi Narapidana Narkotika dan Psikotropika dalam Persfektif Hukum Positif - Saskya Faramita; Arrum Budi Leksono (Syntax Corporation, 2023)
Convicted drug abusers who serve prison sentences have rights protected by human rights and the law, one of which is the granting of remission. Remission is a reduction in the period of criminal service given to Prisoners and Criminal Children who meet the conditions specified in laws and regulations. Based on the above, the problem that will be discussed in this writing is how the provisions and conditions that must be met regarding the provision of remission for prisoners convicted of committing narcotic crimes and narcotic precursors, psychotropic drugs according to applicable law. As for the research method used is a normative research method which of course focuses on literature research to obtain secondary data from legal materials. The normative approach is carried out by reviewing the provisions or applicable laws and regulations. The results of the study that the implementation of the provision of Remission for drug offenders has been regulated in Government Regulation Number 99 of 2012 concerning the Second Amendment to Government Regulation Number 32 of 1999 concerning Terms and Procedures for the Implementation of the Rights of Conditional Assisted Citizens, as stated in article 34 paragraph (2), and article 34A paragraph paragraph 1 letter a and paragraph 2.